Techno-economic analysis of unsaturated polyester production from waste PET - Aleksandar D. Marinković; Milica Rančić (Zaštita Materijala)
Unsaturated polyester resins (UPe) were synthesized from maleic anhydride and products of glycolysis, obtained by polyethylene terephthalate (PET) depolymerization with dipropylene glycol (DPG) in the presence of tetrabutyl titanate catalyst. Waste PET glycolyzed product and UPes were characterized by FTIR and NMR spectroscopy, elemental analysis, acid value (AV), hydroxyl value (HV) and iodine value. Nanocomposites, based on unsaturated polyester resins and hexamethyldisilazane modified silica nanoparticles, were prepared with intention to show one of valuable applicative commercialization of UPe resin. In order to determine potential of the possible implementation of developed new technology for UPe production some aspect of techno- economic analysis was analyzed. Economic potential/benefit and process profitability of the presented technology was based on the use of recycled raw input materials, i.e. waste PET, which is one of the most effective ways to save natural resources, protect the environment, and save money. Principles of green economy was incorporated in the results of developed UPe production technology which is related to both environmental protection and profitability achievement with no additional negative impact to environment, i.e. pollution decrease without negative effect of implemented technology.